2010
DOI: 10.18388/abp.2010_2427
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the inhibitory effects of purine nucleotides and carboxyatractylate on the uncoupling protein-3 and adenine nucleotide translocase.

Abstract: Uncoupling proteins (UCPs) mediate fatty acid-induced proton cycling in mitochondria, which is stimulated by superoxide and inhibited by GDP. Fatty acid anions can also be transported by adenine nucleotide translocase (ANT), thus resulting in the uncoupling of oxidative phosphorylation. In the present work, an attempt was made to distinguish between the protonophoric activity of UCP3 and that of ANT using inhibition analysis. This study was carried out using mitochondria from skeletal muscles of hibernating Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The inhibitory effect of CATR towards other carrier (citrate carrier) than ANT has also been reported [50]. However, it has also been reported that CATR does not influence the GDP binding to UCP2 [12] and does not inhibit UCP1 action [34]. In summary, if CATR and GDP are not specific for their classical targets, measurements focused on UCP inhibition should not be performed in the presence of GDP and CATR.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory effect of CATR towards other carrier (citrate carrier) than ANT has also been reported [50]. However, it has also been reported that CATR does not influence the GDP binding to UCP2 [12] and does not inhibit UCP1 action [34]. In summary, if CATR and GDP are not specific for their classical targets, measurements focused on UCP inhibition should not be performed in the presence of GDP and CATR.…”
Section: Resultsmentioning
confidence: 99%
“…Both UCP-1 and ANT can be inhibited by purine nucleotides such as GDP [ 107 ]. The binding of GDP to UCP-1 is dependent on pH and is optimal at pH 7.0.…”
Section: Mitochondrial Uncoupling Proteins and Metabolites Crosstamentioning
confidence: 99%
“…As demonstrated in isolated rat muscle cells, this effect might rely on superoxide anion production, NFκB activation and iNOS induction (NO production) [ 117 ]. However, the role of UCP-3 as a functional uncoupling protein is still debated and controversial [ 107 ]. Another mechanism by which FFAs could control mitochondrial uncoupling in brown adipocytes is through a direct effect on UCP-1.…”
Section: Mitochondrial Uncoupling Proteins and Metabolites Crosstamentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, GDP inhibition of proton leak was reported. 5 One mM GDP stimulation of respiration and decrease of the membrane potential in isolated mitochondria were observed. 6 Cyclic nucleoside diphosphate ribose, such as cyclic adenosine 5 0 -diphosphate ribose (cADPR), a potent intracellular-Ca 2+ -mobilizing second messenger, is produced enzymatically from nicotinamide adenine dinucleotide (NAD + ) by ADP-ribosyl cyclases.…”
mentioning
confidence: 98%